Risk Factors of Ventilator-Associated Pneumonia in Critically III Patients - Wu, Diling; Wu, Chenfang; Zhang, Siye; Zhong, Yanjun (Frontiers in Pharmacology, 2019)
Ventilator-associated pneumonia (VAP), a hospital acquired pneumonia that occurs more than 48 hours after mechanical ventilation, is a common complication of mechanical ventilation with a high mortality rate. VAP can cause patients to have difficulty weaning off the ventilator and to stay in the hospital longer, which results in a huge financial burden to patients and a huge demand for medical resources. Several strategies, such as drugs including chlorhexidine, β-lactam antibiotics and probiotics, have been used to prevent VAP in clinic. The incidence and the mortality rate of VAP have been decreased with the development of preventative strategies in the past decades, but VAP remains one of the most common causes of nosocomial infections and death in the intensive care unit. Current challenges in the management of VAP involved the lack of a gold standard for diagnosis, the absence of effective preventative strategies, and the rise in antibiotic resistance. Therefore, in order to reduce the incidence of VAP and improve the outcome of patients with mechanical ventilation, it is necessary to clarify the risk factors of VAP for clinical prevention and control of VAP. This paper reviews the international risk factors of VAP occurrence reported in recent years, including patient characteristics, increased mechanical ventilation time and prolonged length of hospital stay, disorders of consciousness, burns, comorbidities, prior antibiotic therapy, invasive operations, gene polymorphism, and mentions the corresponding preventive measures. Each factor is not only an independent risk factor of VAP, but also has an influence on each other. A better understanding of risk factors for VAP is helpful for predicting the occurrence of VAP, improving the prevention and control of VAP, and reducing the morbidity and mortality rates of patients with VAP.